Dynamic Changes in DNA Methylation in Ischemic Tolerance - Meller, Robert; Pearson, Andrea; Simon, Roger P. (Frontiers in Neurology, 2015)
Epigenetic mediators of gene expression are hypothesized to regulate transcriptomic responses to preconditioning ischemia and ischemic tolerance. Here we utilized a methyl-DNA enrichment protocol and sequencing (ChIP-seq) to identify patterns of DNA methylation in an established model of ischemic tolerance in neuronal cultures (oxygen and glucose deprivation: OGD). We observed an overall decrease in global DNA methylation at 4h following preconditioning ischemia (30min OGD), harmful ischemia (120min OGD) and in ischemic tolerant neuronal cultures (30min OGD, 24h recovery, 120min OGD). We detected a smaller cohort of hypermethylated regions following ischemic conditions, which were further analyzed revealing differential chromosomal localization of methylation, and a differential concentration of methylation on genomic regions. Together these data show that the temporal profiles of DNA methylation with respect to chromatin hyper – and hypo-methylation following various ischemic conditions, are highly dynamic and may reveal novel targets for neuroprotection.